Robust, Causal, and Incremental Approaches to Investigating Linguistic Adaptation - Roberts, Seán G. (Frontiers in Psychology, 2018)
This paper discusses the maximum robustness approach for studying cases of adaptation in language. We live in age where we have more data on more languages than ever before, and more data to link it with from other domains. This should make it easier to test hypotheses involving adaptation, and also to spot new patterns that might be explained by adaptation. However, there is not much discussion of the overall approach to research in this area. There are outstanding questions about how to formalise theories, what the criteria are for directing research and how to integrate results from different methods into a clear assessment of a hypothesis. This paper addresses some of those issues by suggesting an approach which is causal, incremental and robust. It illustrates the approach with reference to a recent claim that dry environments select against the use of precise contrasts in pitch. Study 1 replicates a previous analysis of the link between humidity and lexical tone with an alternative dataset and finds that it is not robust. Study 2 performs an analysis with a continuous measure of tone and finds no significant correlation. Study 3 addresses a more recent analysis of the link between humidity and vowel use and finds that it is robust, though the effect size is small and the measurement robustness is only moderate. Methodological robustness of the hypothesis is addressed by suggesting additional approaches including iterated learning, a historical case study, corpus studies and studying individual speech.